2022
DOI: 10.1186/s12887-021-03088-y
|View full text |Cite
|
Sign up to set email alerts
|

Study protocol for reducing disparity in receipt of mother’s own milk in very low birth weight infants (ReDiMOM): a randomized trial to improve adherence to sustained maternal breast pump use

Abstract: Background Black very low birth weight (VLBW; < 1500 g birth weight) and very preterm (VP, < 32 weeks gestational age, inclusive of extremely preterm, < 28 weeks gestational age) infants are significantly less likely than other VLBW and VP infants to receive mother’s own milk (MOM) through to discharge from the neonatal intensive care unit (NICU). The costs associated with adhering to pumping maternal breast milk are borne by mothers and contribute to this disparity. This randomized co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Certainly, longer inter-pump intervals contribute to decreased MOM synthesis via the autocrine/paracrine regulatory pathways and the lack of frequent suckling-induced prolactin secretion from the pituitary ( 60 , 61 ). While we did not routinely have pumping data available on day 5 due to the enrollment time frame through day 6 for ReDiMOM ( 52 ), we found that women were unlikely to pump in the early morning after week 1.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Certainly, longer inter-pump intervals contribute to decreased MOM synthesis via the autocrine/paracrine regulatory pathways and the lack of frequent suckling-induced prolactin secretion from the pituitary ( 60 , 61 ). While we did not routinely have pumping data available on day 5 due to the enrollment time frame through day 6 for ReDiMOM ( 52 ), we found that women were unlikely to pump in the early morning after week 1.…”
Section: Discussionmentioning
confidence: 89%
“…Although our previous research has demonstrated similar rates of MOM provision at NICU discharge by White and Hispanic mothers ( 35 ), the current data demonstrate that the pumping behavior between White and Hispanic mothers are initially similar but then diverge around 4–6 weeks postpartum. Mothers in this study were enrolled in the ReDiMOM trial, for which randomization was stratified by maternal race/ethnicity and infant GA ( 52 ). Therefore, despite the economic intervention available to the intervention arm, the three racial/ethnic groups were similarly distributed between the control and intervention study arms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data suggest that some mothers of PT infants may return to work before their PT infant is discharged from the hospital. Returning to work while providing MOM requires the use of a breast pump to continue lactation processes due to physical separation from the infant, and exclusive or partial breast pump use incurs significant out-of-pocket and time (opportunity) costs [ 60 ]. A very small proportion of women have health-related contraindications to providing MOM, thus considerations regarding returning to work and decisions about MOM provision affect most mothers of PT infants who plan to return to work [ 20 , 61 ].…”
Section: The Interplay Between Work and Mom Provision In Mothers Of P...mentioning
confidence: 99%
“…Since low birth weight and very preterm infants generally do not receive mothers' milk, poor households may find the costs associated with pumping maternal breast milk unaffordable [17]. It is presumed that offsetting the maternal costs of pumping breast milk through subsidies or other alternatives may sustain breastfeeding [17].…”
mentioning
confidence: 99%